Integrated clinicomolecular characterization identifies RAS activation and CDKN2A deletion as independent adverse prognostic factors in cancer of unknown primary. Issue 11 (11th March 2020) - Bochtler, Tilmann; Reiling, Anna; Endris, Volker; Hielscher, Thomas; Volckmar, Anna‐Lena; Neumann, Olaf; Kirchner, Martina; Budczies, Jan; Heukamp, Lukas C.; Leichsenring, Jonas; Allgäuer, Michael; Kazdal, Daniel; et al.
Abstract : Cancer of unknown primary (CUP) denotes a malignancy with histologically confirmed metastatic spread while the primary tumor remains elusive. Here, we address prognostic and therapeutic implications of mutations and copy number variations (CNVs) detected in tumor tissue in the context of a comprehensive clinical risk assessment. Targeted panel sequencing was performed in 252 CUP patients. 71.8% of patients had unfavorable CUP according to ESMO guidelines. 74.7% were adeno‐ and 13.7% squamous cell carcinomas. DNA was extracted from microdissected formalin‐fixed, paraffin‐embedded tissues. For library preparation, mostly multiplex PCR‐based Ion Torrent AmpliSeq™ technology with Oncomine comprehensive assays was used. Most frequent genetic alterations were mutations/deletions of TP53 (49.6%), CDKN2A (19.0%) and NOTCH1 (14.1%) as well as oncogenic activation of KRAS (23.4%), FGFR4 (14.9%) and PIK3CA (10.7%). KRAS activation was predominantly found in adenocarcinomas ( p  = 0.01), PIK3CA activation in squamous cell carcinomas ( p  = 0.03). Male sex, high ECOG score, unfavorable CUP, higher number of involved organs and RAS activation predicted decreased event‐free and overall survival in multivariate analysis. Deletions of CDKN2A were prognostically adverse regarding overall survival. TP53 mutations did not significantly influence prognosis in the overall cohort, but worsened prognosis in otherwise favorable CUP subtypes. Although not standard in CUP, for 17/198 (8.6%) patients molecularly targeted treatment was recommended and 10 patients (5.1%) were treated accordingly. In conclusion, besides the identification of drug targets, panel sequencing in CUP is prognostically relevant, with RAS activation and CDKN2A deletion emerging as novel independent risk factors in a comprehensive assessment with clinicopathological data. Abstract : What's new? While some cancers of unknown primary (CUP) respond to treatment, most have poor survival rates. In this study, the authors used next‐generation sequencing (NGS) to identify specific genetic mutations that indicate a poorer prognosis in CUP. These included CDKN2A deletion and RAS activation, while TP53 mutations indicated poor prognosis mainly in squamous cell carcinoma CUP and in clinically favorable CUP subtypes. NGS results were also able to guide targeted treatment in some CUPs, demonstrating that routine NGS‐based sequencing can enable access to individualized treatment in clinical practice, outside clinical trials.